The Concept of Cross Ventilation in the Type of House Growing Model 21m2 - Dyan Agustin; Niniek Anggriani; Erwin Djuni (Future Science)
21 m2 type housing is a house provided by the developer with a limited area. The available space is very limited both in terms of area and type of space that is only one bedroom, bathroom and shared space. While the activities that occur in the process of inhabiting are quite numerous and complex. This is what causes nearly 90% of residents of type 21m2 homes to renovate / add space to their homes. In the field observations, it was found that 86% of the 21m2 residents of the houses who had renovated their houses had not paid attention to the matter of natural ventilation so that their occupancy felt hot. For this reason, we need a cross-brushing concept on a 21m2 type of home design growth model that provides a solution in terms of effective ventilation design in order to optimize natural ventilation in buildings. In this research, the method used is descriptive exploratory method that is describing the object as it is, namely some studies of the shape and position of the occupancy of a residential type 21m2 that has undergone renovation. Then the data is analyzed qualitatively and quantitatively to clarify the qualitative. In accordance with the purpose of the research, which is to find the concept of cross-sectioning on a 21m2 residential growth model design model, a deeper survey was conducted, measurements and data collection through cameras and sketches. The results showed several cross-air concepts in the home design model of growth with optimal openings design analysis in terms of natural ventilation. The concept of cross handling in a 21m2 type of growing house will benefit the comfort of residents of a 21m2 type of house as well as various parties both the general public, residents, developers and researchers in the field of housing and interior.